Characteristics, predictors and outcomes after unprotected left main stem primary percutaneous coronary intervention. (25th November 2020) - Mehmedbegovic, Z; Milasinovic, D; Jelic, D; Zobenica, V; Radomirovic, M; Vratonjic, J; Zaharijev, S; Pavlovic, A; Vukcevic, V; Asanin, M; Stankovic, G
Abstract: Background: Reports about outcomes of patients undergoing primary percutaneous coronary intervention (PCI) for unprotected left main (ULM) coronary artery are limited. We aimed to investigate the characteristics, in-hospital and the long-term outcomes of these patients. Methods: From a high-volume, single-centre, prospective registry, in a period from 2009–2019, we identified 111 pts (0.96%) who undergone primary PCI for ULM culprit lesion. The short- and the long-term outcomes in this subset was evaluated and compared to 9463 (82.5%) patients undergoing pPCI for lesions located in other segments (Non-LM group). Technical success was defined as final TIMI 3 flow in both, left main and distal vessels, anterior descending and circumflex artery, without significant residual stenosis (>20% following balloon angioplasty or stent implantation) and side branch compromise (residual stenosis >75%). Results: Patients with ULM were older and more likely to present as Non-ST-elevation MI (77% vs. 93%; p<0.000) and in cardiogenic shock (40% vs. 2.2%; p<0.000), having less occlusive disease with TIMI 0–1 flow prior to PCI (44% vs. 78%; p<0.000) compared to Non-LM patients. Also, greater procedure complexity was observed with longer lesions >20mm (50% vs. 29%; p<0.000), more intraluminal thrombus (86% vs. 45%; p<0.000), greater number (1, 48±0, 9 vs. 1, 28±0, 7; p<0.01) and longer stents (30, 5±15, 8 vs. 27, 4±14, 3; p=0.028), more GP IIb/IIIa inhibitors (32% vs. 23%; p=0.022), intra-aortic counterpulsations (7% vs. 0.6%; p<0.000) and contrast media used (202±96 vs. 172±66; p<0.000) in ULM group. Despite obtaining comparable rates of final TIMI 3 flow in main branch (91.9% vs. 95.4%; p=0.084), patients with LMCA had significantly higher in-hospital (27% vs. 4.7%: p<0.000), and one-year all-cause mortality (41% vs. 11%: p<0.000), but for the remaining duration of clinical follow-up (available for 97.8% pts, median duration 51±37 months) survival rates were comparable between ULM and Non-LM pts (18% vs. 15%: p=0.506) (Figure 1). Regression analysis showed that final TIMI 3 in main branch at 30 days (HR 0.05 [95% CI 0.005–0.604]; p=0.018), while peri-procedural cardiogenic shock (hazard ratio (HR) 8.3 [95% CI 2.5–28.1]; p=0.001), creatinine clearance <60 ml/min (HR 7.5 [95% CI 2.3–25.1]; p=0.001) and technical success (HR 0.16 [95% CI 0.45–0.57]; p=0.005) at 5 years, independently predicted mortality in ULM patients. Conclusions: Despite performance of primary PCI, patients with MI due to ULM lesions are associated with worse in-hospital and one-year mortality but following that period mortality was comparable to control group. Suboptimal final coronary flow best predicted the 30 day, while peri-procedural cardiogenic shock, renal dysfunction at admission and suboptimal technical procedure result, predicted long-term mortality in these patients. Funding Acknowledgement: Type of funding source: None